Shape- and dimensional stability of solid wood panels made from heat-treated lime wood strips - Olarescu, M. C.; Campean, M.; Cosereanu, C. (Springer Science and Business Media LLC, 2016)
The paper presents the results of an experimental research performed with solid wood panels made from heat-treated and untreated lime wood (Tilia cordata Mill.) strips and then subjected to open-air exposure for 3 months. The dimensions of the panels were measured by means of an OPTODesQ Measurement Table, first after conditioning and sanding, then after each month of open-air exposure in order to assess their shape- and dimensional stability. After 3 months, the panels made from heat-treated wood strips showed up to 70% lower volumetric swelling and up to 143% lower flatness deviation than the panels made from untreated strips.